Crimean Mosaic: Spatial Analysis of the Structure and Dynamics of the Regional Museum Network - Mazur, Lyudmila N. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
Referring to the data of the author’s database of Crimean museums, this article offers a spatial analysis of the structure and dynamics of the museum network. The official digital resources (websites) of the Ministry of Culture of the Russian Federation, the Museums of Russia portal, the website of the Private and Folk Museums of Russia, and the websites of municipalities are used as the main sources of information. The database information makes it possible to reconstruct the images of the region, taking into account their geographic reference. The museum landscape of the region forms a polyphonic historical and cultural image of Crimea, which is divided into five clusters (zones): literary and historical (Southern coast of Crimea); military-historical (Sevastopol); historical and local history (steppe Crimea); historical and archaeological (Kerch Peninsula); historical and ethnographic (mountainous Crimea). Clusters differ in the structure of the museum network and the historical dynamics of its formation. The author analyses the features of the formation of each museum cluster and the images of the past it broadcasts. The image of the war is most intensively present in the museums of Sevastopol and Balaklava as the places of the deployment of the Black Sea Fleet. Literary Crimea is concentrated in cities and urban-type settlements of the southern coast of Crimea, where many famous writers rested, were treated, and created their works. Images of the Soviet past are disseminated by local history museums of the steppe Crimea. The ancient civilization and medieval Crimea are represented in the Kerch cluster and partly by the historical and archaeological museums of the South Coast and the mountainous Crimea. And, finally, the national (Crimean-Tatar) image of Crimea is preserved in the museums of Bakhchisaray and Simferopol. Such a complex mosaic of Crimean images is the result of the influence of external and internal factors — the richness and diversity of the historical and cultural heritage of the region formed over the centuries and the zigzags of the state cultural policy. The change of statehood over the twentieth century (imperial, Soviet, post-Soviet — Ukrainian and Russian — periods) has left its mark on the museum space of Crimea.